Stability-Diversity Tradeoffs Impose Fundamental Constraints on Selection of Synthetic Human VH/VL Single-Domain Antibodies from In Vitro Display Libraries - Henry, Kevin A.; Kim, Dae Young; Kandalaft, Hiba; Lowden, Michael J.; Yang, Qingling; Schrag, Joseph D.; Hussack, Greg; MacKenzie, C. Roger; Tanha, Jamshid (Frontiers in Immunology, 2017)
Human autonomous VH/VL single-domain antibodies (sdAbs) are attractive therapeutic molecules, but often suffer from suboptimal stability, solubility and affinity for cognate antigens. Most commonly, human sdAbs have been isolated from in vitro display libraries constructed via synthetic randomization of rearranged VH/VL domains. Here, we describe the design and characterization of three novel human VH/VL sdAb libraries through a process of: (i) exhaustive biophysical characterization of 20 potential VH/VL sdAb library scaffolds, including assessment of expression yield, aggregation resistance, thermostability and tolerance to CDR substitutions; (ii) in vitro randomization of the CDRs of three VH/VL sdAb scaffolds, with tailored amino acid representation designed to promote solubility and expressibility; and (iii) systematic benchmarking of the three VH/VL libraries by panning against five model antigens. We isolated ≥1 antigen-specific human sdAb against four of five targets (13 VHs and 7 VLs in total); these were predominantly monomeric, had antigen-binding affinities ranging from 5 nM – 12 µM (average: 2 – 3 µM), but had highly variable expression yields (range: 0.1 – 19 mg/L). Despite our efforts to identify the most stable VH/VL scaffolds, selection of antigen-specific binders from these libraries was unpredictable (overall success rate for all library-target screens: ~53%) with a high attrition rate of sdAbs exhibiting false positive binding by ELISA. By analyzing VH/VL sdAb library sequence composition following selection for monomeric antibody expression (binding to protein A/L followed by amplification in bacterial cells), we found that some VH/VL sdAbs had marked growth advantages over others, and that the amino acid composition of the CDRs of this set of sdAbs was dramatically restricted (bias towards Asp and His and away from aromatic and hydrophobic residues). Thus, CDR sequence clearly dramatically impacts the stability of human autonomous VH/VL immunoglobulin domain folds, and sequence-stability tradeoffs must be taken into account during the design of such libraries.